Electrophysiological examination of transmitter release in non-quantal form in the mouse diaphragm and the activity of membrane ATP-ase - Vyskocil, F; Illés, P (Physiologia Bohemoslovaca, 1978)
The subsynaptic area of mouse diaphragm fibres was hyperpolarized by 1--2 mV during local curarization of the junctional zone in the presence of the reversible anticholinesteraze prostigmine (6 X 10(-6) M), or after treatment of the muscle with organophosphate cholinesterase inhibitor Soman. In a solution containing 5 mM K+ the mean hyperpolarization was 1.1 +/- 0.27 mV at mean resting potential--70 mV. After adding 2 X 10(-5) M ouabain the hyperpolarization increased to 1.5 +/- 0.25 mV. Removal of potassium ions from the bathing medium also increased curare induced hyperpolarization to 1.80 +/- 0.40 mV. Reactivation of membrane ATP-ase by addition of K+ after a period in K+-free medium reduced the hyperpolarization to zero, where measurements were performed 10--20 min after the readdition. It was concluded that spontaneous non-quantal leakage of acetylcholine occurs at the mouse neuromuscular junction, as it does in the frog (ref. Katz and Miledi 1977). Conditions which block the Na+-K+-dependent ATP-ase of nerve terminals increased the continuous leakage of ACh and activation of the pump decreased it.
Keywords: cholinesterasové inhibitory; Diaphragm; techniky in vitro; membránové potenciály; Cholinesterase Inhibitors; Membrane Potentials; zvířata; Mice; draslík; neostigmin; ouabain; elektrofyziologie; Neurotransmitter Agents; sodíko-draslíková ATPasa; Potassium; Tubocurarine; adenosintrifosfatasy; tubokurarin; Ouabain; Adenosine Triphosphatases; neurotransmiterové látky; myši; bránice; Electrophysiology; Animals; Neostigmine; In Vitro Techniques; Sodium-Potassium-Exchanging ATPase